Biomarker-based reconstructions of Holocene lake-level changes at Lake Gahai on the northeastern Tibetan Plateau. (April 2014) - He, Yuxin; Zheng, Yanwei; Pan, Anding; Zhao, Cheng; Sun, Yuanyuan; Song, Mu; Zheng, Zhuo; Liu, Zhonghui
Holocene hydrological changes in regions dominated by the westerlies significantly differ from those by the Asian summer monsoon. The high-elevated northeastern Tibetan Plateau, located in between, is likely influenced by the interactions of both circulation systems. Here, we attempt to use biomarkers, n -alkanes and alkenones, to reconstruct Holocene lake-level changes at Lake Gahai in the Qaidam Basin. We choose a sediment core drilled at the lake shore, where biomarkers would be sensitive to lake-level changes. The n -alkane records show high average chain length (ACL), high carbon preference index (CPI), and low proportion of aquatic macrophyte (Paq ) values at 7–2 kyr (thousand calibrated years ago) with peaked values around 6 kyr, whereas low ACL, low CPI, and high Paq values occurred after 2 kyr and before 7 kyr. No alkenones were detected at 7–2 kyr, suggesting that lake level at this period was incapable of constantly reaching to the coring site. Therefore, combined results provide unambiguous evidence of relatively low lake level at 7–2 kyr, probably lowest at ~6 kyr. Holocene lake-level changes in this marginal region thus display a different pattern from either of the core regions dominated by the westerlies (anti-phase) and the Asian summer monsoon (out-of-phase). We suggest that in the arid marginal region, temperature-induced evaporation could significantly affect regional hydrological balance, resulting in the discrepancy with the Holocene long-term precipitation decreasing trend in Asian monsoon-dominated regions.